2020
DOI: 10.1186/s13014-020-01685-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and toxicity of re-irradiation for esophageal cancer patients with locoregional recurrence: a retrospective analysis

Abstract: Introduction There is no standard treatment for locoregional recurrent (LR) esophageal squamous cell carcinoma (ESCC) patients treated with radiotherapy (RT) previously. This retrospective study aimed to examine the efficacy and toxicity of re-irradiation (re-RT) for ESCC patients with LR. Patients and methods A total of 252 patients were enrolled. Gross tumor volumes for re-RT were defined using contrast enhanced computed tomography and/or positron emission tomography/computed tomography. Overall survival (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
9
1
Order By: Relevance
“…In our study, for instance, only 1 case of pneumonitis (3.2%) was noted among patients who received PBT, compared with up to 12.8% rates of pneumonitis with conventional photon RT in the reRT setting. 10 Although PBT typically limits the dose to normal tissues more effectively compared with conformal photon-based therapies such as IMRT, in the setting of reRT, PBT still delivers a high cumulative dose to areas of overlap with the prior RT field. Both PBT and IMRT are advanced radiation techniques aimed at precisely targeting tumors while striving to minimize exposure to surrounding healthy tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, for instance, only 1 case of pneumonitis (3.2%) was noted among patients who received PBT, compared with up to 12.8% rates of pneumonitis with conventional photon RT in the reRT setting. 10 Although PBT typically limits the dose to normal tissues more effectively compared with conformal photon-based therapies such as IMRT, in the setting of reRT, PBT still delivers a high cumulative dose to areas of overlap with the prior RT field. Both PBT and IMRT are advanced radiation techniques aimed at precisely targeting tumors while striving to minimize exposure to surrounding healthy tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, additional RT to a previously irradiated field can pose a significant challenge because of the dosimetric constraints of adjacent critical structures and is associated with an increased incidence of treatment-related toxicity, especially with photon-based reRT. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…The OS of these patients in the RT group was 19.43 months. Several studies have been reported of locoregional recurrent esophageal cancer treated with radiotherapy or chemoradiotherapy, with an OS of 7.0–24.3 months [13] , [14] , [15] , [16] , [17] , [18] , [19] . The OS in our study was estimated from the initiation of immunotherapy not the start of radiation or the date of relapse like the studies mentioned above, so we recalculated the OS of locoregional recurrence patients in the RT group from the first date of radiation, and the results was 22.60 months (95 % CI: 12.58–32.62), which was only inferior to the 24.3 months in Kobayashi’s study (whose OS was also defined from the start of radiotherapy) [15] .…”
Section: Discussionmentioning
confidence: 99%
“…However, local recurrence (LR) after dCRT was still the main failure pattern (~ 50%) [ 5 , 6 ]. Once recurrence occurs, the survival rate at five-years drops to 0–11% [ 7 ]. It is of great importance to balance disease control and toxicities when considering salvage treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported improvement of symptoms with an objective response rate of 55–91% [ 18 , 19 ]. Usually, Re-RT is used with caution because of poor blood supply, less tumor sensitivity and the increased complications such as esophageal perforation or stenosis [ 7 , 19 , 20 ]. Re-RT has been reported to achieve long-term survival in carefully selected REC patients treated with three-dimensional conformal radiotherapy (3D-CRT) or intensity-modulated radiotherapy (IMRT) technique [ 13 ].…”
Section: Introductionmentioning
confidence: 99%